Alliteration as a Means to Reinforce Orality in Conrad’s Early Marlow Narratives: - - Kujawska-Lis, Ewa (Zagadnienia Rodzajów Literackich / The Problems of Literary Genres, 2019)
https://doi.org/10.26485/ZRL/2018/61.1/6 Joseph Conrad’s narratives featuring Marlow are composed as stories within stories, in which Marlow (the intradiegetic narrator) tells stories to his few listeners (the intradiegetic addresses). Critics have found analogies of these narratives with the Polish gawęda tradition and the English sailor’s yarn, both related to oral story-telling. This paper sets out to look at one literary device — alliteration — found in early works narrated by Marlow (Youth, Heart of Darkness, and Lord Jim), and to indicate that various effects achieved by alliterative phrases (onomatopoeic, emphatic, rhythmical, and autotelic) all contribute to this narrator’s status as an oral performer.